Del "querido amigo" al "partido antigubernativo": la política imperial y la detención de clientes virreinales en la Nueva España, 1746-1768 - Rosenmüller, Christoph (Anuario de Historia de América Latina, 2020)
The viceroy first Count of Revillagigedo (1746-1755) seized the administration of the excise tax (alcabalas) of Mexico City from the merchant guild (consulado) with the assistance of Cathedral Canon Ignacio Felipe Cevallos and a group of merchants. Cevallos and other clients also attained important viceregal support or appointments. When Revillagigedo died, however, Viceroy Marquis de Croix and the investigative judge José de Gálvez (1765-1771) accused Cevallos and seven other former viceregal clients of opposing the expulsion of the Jesuits in 1767. Six of them were sent to Spain. This article traces the fate of these clients in the changing local and imperial settings from Revillagigedo’s term to Gálvez’s Visita General and beyond. While scholars have argued that Croix charged members of an “anti-governmental party”, I show that several of them had originally been pro-government because of their ties to Revillagigedo. I also agree with the scholarship that the Visita General did not exclusively target Creoles and Natives, as it also clashed with a network of former viceregal partisans of various regional extractions, including Spain.
Keywords: Viceroys, Visita General, Social Networks, Reforms, Consulado, Anti-governmental Party, José de Gálvez, Revillagigedo, Croix